Ultra‐high‐resolution 1058‐ppi OLED displays with 2.78‐in size using CAAC‐IGZO FETs with tandem OLED device and single OLED device. Issue 3 (20th March 2016) - Yokoyama, Kohei; Hirasa, Shinichi; Miyairi, Noriko; Dozen, Yoshitaka; Sasaki, Toshiki; Jimbo, Yasuhiro; Toyotaka, Kouhei; Kaneyasu, Makoto; Miyake, Hiroyuki; Seo, Satoshi; Hirakata, Yoshiharu; Yamazaki, Shunpei; et al.
Abstract: We fabricated new 2.78‐in 1058‐ppi organic light‐emitting diode (OLED) displays. The displays used OLED devices with a tandem structure and a single structure and a field effect transistor (FET) using c‐axis aligned crystalline In–Ga–Zn–O (CAAC‐IGZO) for an active layer and employing the 1.5‐µm rule over a glass substrate. Even in the displays with such high resolution exceeding 1000 ppi, crosstalk that was observed in the lower luminance region was suppressed. The displays achieved high color reproducibility and reduced viewing angle dependence. Abstract : We fabricated new 2.78‐in. 1058‐ppi organic light‐emitting diode (OLED) displays. The Q3 displays used OLED devices with a tandem structure and a single structure and a field effect transistor using c‐axis‐aligned crystalline In–Ga–Zn–O for an active layer and employing the 1.5‐µm rule over a glass substrate. The displays achieved high color reproducibility and reduced viewing angle dependence.